Analysis of Breaststroke Technique in Physical Education, Health, and Recreation Students at Karimun University - Fadli Surahman; Hilda Oktri Yeni; Rahmat Sanusi (International Conference on Science, Education, and Technology, 2023)
Observing many students' inadequate ability to effectively and accurately master the breaststroke technique, this study aims to describe the movement analysis in breaststroke technique among Physical Education, Health, and Recreation students at Karimun University. The research focuses on aspects such as body position, arm movement, leg movement, breathing, and coordination. It adopts a quantitative descriptive research design with a population of 30 individuals. The sampling technique used is purposive sampling. Data collection involves direct observation of breaststroke movements by the researcher in the field. After collecting the data, it will be analyzed using quantitative descriptive analysis methods. The research findings are as follows: 1) The ability to master the breaststroke technique can be measured based on the body position indicator, which reaches 62.00%, falling into the "good" category; 2) The ability to master the breaststroke technique can be measured based on the arm movement indicator, which reaches 54.80%, falling into the "sufficient" category; 3) The ability to master the breaststroke technique can be measured based on the leg movement indicator, which reaches 59.93%, falling into the "sufficient" category; 4) The ability to master the breaststroke technique can be measured based on the breathing indicator, which reaches 58.00%, falling into the "sufficient" category; and 5) The ability to master the breaststroke technique can be measured based on the coordination indicator, which reaches 52.67%, falling into the "sufficient" category. Therefore, based on the research results from 30 students, the overall level of mastery in the breaststroke technique is 55.93%, falling into the "sufficient" category.